A comparative study on the macronutrient intake of elite Indian female weightlifters and boxers - Tyagi, P.; Bhushanam, G. V. (International Journal of Physiology, Nutrition and Physical Education, 2021)
Weightlifting & Boxing are weight specific power events which involves high intensity training. Nutrient supply for fueling body stores as well as maintenance of body weight for the desired category is of utmost importance. This study is aimed to assess the energy and macro nutrient intake of elite female Weightlifters & Boxers of SAI and to compare with recommendation of NIN (National Institute of Nutrition) & SAI (Sports Authority of India). Out of a total of 45 sports persons, 22 were weightlifters & 23 were boxers. The compression between sports has been made based on weight category of heavy, middle & light. A questionnaire and 24 hr dietary recall were used to collect data. The mean energy intake was 2835 + 532.91, 2834.66 + 417.18, 2595.33 + 444.93 kcal in boxers of heavy, middle & light weight categories respectively. The mean energy intake was 4789.82 + 787.36, 4335.3 + 836.70 & 3372.18 + 826.13k.cal in weightlifters of heavy middle & light weight categories respectively. The comparison of percentage adequacy with NIN recommendations showed fairly adequate among all weight categories of weightlifters and inadequate among all weight categories of boxers. The mean percentage carbohydrate intake of total energy was 56%, 55% and 51% in heavy, middle and light respectively in boxers and 37%, 47% and 50% in heavy, middle and light respectively in weightlifters. The carbohydrate intake was low in weightlifters of all categories in comparison with boxers against recommendation. On the contrary, in boxing the carbohydrate intake was low only in light weight category. The protein intake was high in all categories of weightlifters compared to boxers and the recommended value. The protein intake was adequate in middle weight category boxers and moderate in high & light weight category boxers. Mean percentage fat intake of total energy was 26%, 24% & 28% in heavy, middle and light weight categories respectively among weightlifters and 31%, 30% & 26% in heavy, middle and light weight categories respectively among boxers. The intake of fat was high in weightlifting in all weight categories and in boxers it was high in middle & light weight categories. Adequate nutritional counselling is required to address the nutrient intake to the players for optimizing their performance.